2006
DOI: 10.29140/jaltcall.v2n1.18
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of mobile phone learning

Abstract: In this article, we discuss weaknesses inherent in mobile phone learning, and factors that limit its viability. (We do not discuss other m-learning devices such as PDAs.) We conclude that, while e-learning has met with some acceptance among educators and is increasingly being implemented, it will be necessary to solve the problems that we discuss before m-learning can become effective, accepted and widely used. Educators who are interested in using mobile phones for learning with their students should be aware… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 6 publications
3
32
0
1
Order By: Relevance
“…High-quality technology has been seen as a barrier in testing and assessment when learning should be considered mobile in the digital era. While the physical characteristics of the mobile device would be thought to play a role, the impacts of the psychological and pedagogical factors are also likely contributing factors [35].…”
Section: Mobile Learningmentioning
confidence: 99%
“…High-quality technology has been seen as a barrier in testing and assessment when learning should be considered mobile in the digital era. While the physical characteristics of the mobile device would be thought to play a role, the impacts of the psychological and pedagogical factors are also likely contributing factors [35].…”
Section: Mobile Learningmentioning
confidence: 99%
“…A previous study claimed that mobile learning is still considered a supplementary method that can help students to learn but not operate as a full learning process, nor can it assume the role of the teacher due to its technical limitations and its inability to replicate human nature [17]. Moreover, another study found that about 95% of students support the use of mobile phones to communicate with classmates and teachers as this is faster than traditional methods [18].…”
Section: Introductionmentioning
confidence: 99%
“…Involving mobile technology in the learning process in developing countries might confront many difficulties resulting in problems of using the technology, one of these being technical challenges [20]. Mobile learning users may encounter difficulties in using this technology when they travel abroad if their destination countries do not follow the same technical standards [17]. Due to the weaknesses of the technology substructure in Africa, inserting M-Learning among postgraduates may face challenges [21].…”
Section: Introductionmentioning
confidence: 99%
“…Early research in m-learning emphasized limitations of the mobile devices [26], such as size of the display, reduced input, small memory, abridged or specific OS version, and lack of standards, which positioned m-learning as a specific case of e-learning [27,28]  Links between the elements: any natural language has typical collocations, exceptions, specific cases that cannot be produced by formal application of grammar rules to a set of terms. In case of professional terminology, some terms may be related closer than others and might benefit from being learned together.…”
Section: M-learning Vs E-learningmentioning
confidence: 99%